EFFECT OF MORDANTS ON COLOR SHADE AND COLOR FASTNESS OF SILK DYED WITH KIKAR AND MADDER BARKS (Biological Sciences - PJSIR, 2004)
The silk fabric was dyed with aqueous extract of Kikar bark (Acacia arabica) and Madder bark (Rubia cordifolia) by using various metal sulphates as mordants. The three techniques of mordanting were used for dyeing the fabric and are known as pre-mordanting, where the fabrics were first mordanted and then dyed with natural dye extract, meta- mordanting (i.e. dyeing in the presence of mordants) and post- mordanting where the dyed fabrics were treated with mordants. The fastness properties i.e. crock fastness, washing fastness and light fastness of the dyed samples were determined and comparison was made for control and samples dyed in the presence of the metal ions. The three fastness of the dyed samples were found to be good to excellent. The color of the dyed silk was investigated on computer color matching system in terms of Reflectance, K/S and CIE lab color values. The effect of different metal ions have been studied with respect to their influence on color shade and fastness properties. The mechanism of mordant interactions with the fabric has been briefly discussed.